iCare Business Plan, Management Project - Saleem, Younus (2016)
Exec Summary iCare is a web based, healthcare consultation service, bringing doctors and HCPs (Health Care Professionals) to internet serving patient. iCare bridges the gap of communication/contact between doctors and patients. iCare makes healthcare access less complex, changing how patients seek medical assistance, information and advice. iCare main value proposition is providing remote video-link consultations to patients anywhere in the world except USA . Patients use a web-based platform (website or App), creating a short profile and select their condition/s from a pre-defined list. Through a list of ‘matching’ Health Care Professionals (HCP’s) a consultation is arranged allowing the patient to book a slot in the HCP’s diary. Patients pay a fixed fee for a fixed consultation time period depending on the rate of the HCP. The patient will be able to choose how they want their consultation, text only chat, voice only chat, or video chat (mainstay of the service). The solution will work on all platforms/devices including computers, tablets and smartphones.